MENINGKATKAN KEMAMPUAN PASSING BOLA VOLI SISWA SMA MELALUI PEMBELAJARAN DENGAN MODEL BERMAIN - Harry Aprianto (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract The aim of this article is to know influence teaching with play volleyball model for increase of capability passing in playing volley ball. This article is the exeperiment with the one group pretest design posttest design The total population in this experiement there are 34 students. The instrument which use to know the capability passing in volleyball is with passing ball test. The analysis technics which use in this exsperiment is test t with level significant 5%. The result of this experiment, show that the influence significant of the teaching with volleyball model which the capability of passing in volleyball with value T count is 9,439 and the value T table is 1,692. Kata kunci : bermain, pembelajaran dengan model bermain, passing bola voli